The psychotropic education and knowledge test for nurses in nursing homes: striving for PEAK performance. (1st November 2016) - Perehudoff, Katrina; Azermai, Majda; Wauters, Maarten; Van Acker, Sandra; Versluys, Karen; Steeman, Els; Petrovic, Mirko
Abstract : Objectives: The p sychotropic e ducation a nd k nowledge test for nurses in a cute geriatric c are (PEAK-AC) measures knowledge of psychotropic indications, doses and adverse drug reactions in older inpatients. Given the low internal consistency and poor discrimination of certain items, this study aims to adapt the PEAK-AC, validate it in the nursing home setting and identify factors related to nurses' knowledge of psychotropics. Method: This study included nurses and nurse assistants employed by nursing homes ( n = 13) and nursing students at educational institutions ( n = 5) in Belgium. A Delphi technique was used to establish content validity, the known groups technique for construct validity ( n respondents = 550) and the test–retest procedure for reliability ( n respondents = 42). Internal consistency and item analysis were determined. Results: The psychotropic education and knowledge test for nurses in nursing homes (PEAK-NH) ( n items = 19) demonstrated reliability (κ = 0.641) and internal consistency (Cronbach's α = 0.773). Significant differences between-group median scores were observed by function ( p < 0.001), gender ( p = 0.019), educational background ( p < 0.001), work experience ( p = 0.008) and continuing education ( p < 0.001) for depression, delirium and pharmacotherapy topics. Items were acceptably difficult ( n items = 15) and well-functioning discriminators ( n items = 17). Median PEAK-NH score was 9/19 points (interquartile range 6–11 points). Respondents' own estimated knowledge was related to their PEAK-NH performance ( p < 0.001). Conclusion: The PEAK-NH is a valid and reliable instrument to measure nurses' knowledge of psychotropics. These results suggest that nurses have limited knowledge of psychotropic use in nursing homes and are aware of their knowledge deficits. The PEAK-NH enables educational initiatives to be targeted and their impact on nurses' knowledge to be tracked.